O efeito de diferentes instrumentos de glide path na resistência à fadiga cíclica de instrumentos reciprocantes após três utilizações - Scherer, André Schröder (2021)
During the endodontic procedure, the clinician is susceptible to the occurrence of some accidents such as root perforations, deviations and instrument fractures. In order to avoid fractures of mechanized instruments, the use of glide path instruments was recommended to allow the action of the final preparation instrument in a free manner. The present study aims to evaluate the effect of different glide path instruments on the cyclic fatigue resistance of reciprocating endodontic instruments after three uses in mandibular molars. Eighteen Wave One Gold Primary reciprocating instruments were selected and randomly divided into three groups according to the glide path instrument: G1 – manual file K #15, G2 – Wave One Glider reciprocating instrument, and G3 (control group) – glide path was not performed. The reciprocating instruments were tested on mandibular molars and subdivided into three other groups: a new instrument, an instrument with a previous single-use and an instrument with two previous uses. After the endodontic instrumentation, the instruments were subjected to the cyclic fatigue resistance test using a appropriate tool. The data were submitted to the Shapiro-Wilk test, and subsequently the Kruskal-Wallis test with a significance level of 5%. The results showed no statistical difference between the groups. Thus, it was concluded that the creation of a glide path did not affect the cyclic fatigue resistance of the reciprocating instrument. In addition, the reuse of final preparation instruments up to two times proved to be safe since no fractures were observed in the tested instruments.